SOCIAL CONDITION OF PARIS DURING FRENCH REVOLUTION AS REFLECTED IN CHARLES DICKENS’ A TALE OF TWO CITIES - Rahmad, Ichsan; Setyawan, Ari (Wiralodra English Journal, 2018)
The objectives of the study are to describe the social condition of the novel and the other sources and to analyze the novel by means of sociological aspect to know the social condition in Paris during the French revolution in the novel A tale of Two Cities by Charles Dickens, focusing on the portrait of social condition in Paris. The methods used in this research are observation and documentation. The research findings are; first, there are injustice conditions before the revolution have done by the aristocrats such as politic, economy, oppression, and so on which have to face by the citizens. Second, all the injustice has done by aristocrats made social disappointment and led to revolution. Third, the government, even in absolute monarchy term, could be ruined by united people in the same purpose; they wanted better change for their country.